Campylobacter fetus meningitis associated with eating habits of raw meat and raw liver in a healthy patient: A case report and literature review. (2018) - Ishihara, Ayaka; Hashimoto, Etaro; Ishioka, Haruhiko; Kobayashi, Hiroyuki; Gomi, Harumi
Abstract: Meningitis caused by the zoonotic pathogen Campylobacter fetus in immunocompetent adults is rare. We report a 48-year-old Japanese woman with no underlying disease who was found to have meningitis caused by C. fetus . Both C. fetus subsp. fetus and C. fetus subsp. venerealis were isolated from the cerebrospinal fluid culture. The mode of infection in our patient was considered to be associated with the consumption of raw beef and raw cattle liver on a regular basis. Public awareness and education to avoid the consumption of raw or undercooked meat might help prevent C. fetus meningitis.